Life-prolonging treatment restrictions and outcomes in patients with cancer and COVID-19: an update from the Dutch Oncology COVID-19 Consortium. (January 2022) - de Joode, Karlijn; Tol, Jolien; Hamberg, Paul; Cloos, Marissa; Kastelijn, Elisabeth A.; Borgers, Jessica S.W.; Nuij, Veerle J.A.A.; Klaver, Yarne; Herder, Gerarda J.M.; Mutsaers, Pim G.N.J.; Dumoulin, Daphne W.; Oomen-de Hoop, Esther; et al.
Abstract: Aim of the study: The coronavirus disease 2019 (COVID-19) pandemic significantly impacted cancer care. In this study, clinical patient characteristics related to COVID-19 outcomes and advanced care planning, in terms of non-oncological treatment restrictions (e.g. do-not-resuscitate codes), were studied in patients with cancer and COVID-19. Methods: The Dutch Oncology COVID-19 Consortium registry was launched in March 2020 in 45 hospitals in the Netherlands, primarily to identify risk factors of a severe COVID-19 outcome in patients with cancer. Here, an updated analysis of the registry was performed, and treatment restrictions (e.g. do-not-intubate codes) were studied in relation to COVID-19 outcomes in patients with cancer. Oncological treatment restrictions were not taken into account. Results: Between 27th March 2020 and 4th February 2021, 1360 patients with cancer and COVID-19 were registered. Follow-up data of 830 patients could be validated for this analysis. Overall, 230 of 830 (27.7%) patients died of COVID-19, and 60% of the remaining 600 patients with resolved COVID-19 were admitted to the hospital. Patients with haematological malignancies or lung cancer had a higher risk of a fatal outcome than other solid tumours. No correlation between anticancer therapies and the risk of a fatal COVID-19 outcome was found. In terms of end-of-life communication, 50% of all patients had restrictions regarding life-prolonging treatment (e.g. do-not-intubate codes). Most identified patients with treatment restrictions had risk factors associated with fatal COVID-19 outcome. Conclusion: There was no evidence of a negative impact of anticancer therapies on COVID-19 outcomes. Timely end-of-life communication as part of advanced care planning could save patients from prolonged suffering and decrease burden in intensive care units. Early discussion of treatment restrictions should therefore be part of routine oncological care, especially during the COVID-19 pandemic. Highlights: This registry identified risk factors of a fatal outcome of coronavirus disease 2019 (COVID-19). 50% of the patients had restrictions regarding life-prolonging treatment. Most of the patients with treatment restrictions had risk factors of fatal COVID-19. Treatment restrictions could reduce patients' suffering and the burden of intensive care units. End-of-life communication should be part of routine oncological care.